Crisis Management of Brawijaya University - Arsih Amalia Chandra Permata; Maulina Pia Wulandari; Rachmat Kriyantono (GoAcademica Research & Publishing, 2020)
The aim to be achieved is to know the efforts of crisis management. The research was conducted at the University of Brawijaya in 2010-2019, based on the view of the Rector of the University of Brawijaya during his tenure, as well as a plan to deal with the crisis at Brawijaya University in 2020-2025. This evaluative study was conducted using a qualitative approach and in-depth interview methods. The informant interviewed by the Chancellor who served in the period 2010-2019, the head of UB's Public Relations. The results of this study will describe or construct in-depth interviews with research subjects so that they can provide a clear picture of Crisis Management in UB since 2010-2019. The method used in this research is indepth interviews (intensive interviews) or intensive interviews (intensive interviews) and most are not structured. To maintain data quality using checking with triangulation. The results showed that the crisis at the university which was classified specifically, had not been interpreted as a crisis in the body of the organization itself, the role of public relations was also more focused on fostering good relations with the media.